Penggunaan Model Problem Based Learning Pada Materi Sebaran Flora dan Fauna untuk Meningkatkan Hasil Belajar Geografi Siswa Kelas XI SMA Negeri 12 Kendari - Serling Saramida Daati; La Ode Amaluddin; Amniar Ati; Surdin Surdin (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Senior High School 12 Kendari is one of the schools in Kendari City with low student learning outcomes. The objectives of this study are: 1) to describe the description of student learning activities; 2) to describe the description of teacher teaching activities; and 3) to determine the improvement in student learning outcomes of class XI-Social Senior High School 12 Kendari with the Problem Based Learning learning model on the Distribution of Flora and Fauna material. This type of research is Classroom Action Research. This study uses qualitative and quantitative descriptive data analysis techniques. The results of the study showed an increase; 1) student learning activities in Cycle I were 2.3 and cycle II increased to 3.4; 2) teacher teaching activities in cycle I were 2.8 in cycle II increased to 3.7; and 3) student learning outcomes in cycle I were 57% increased to 90%. This shows that the application of the Problem Based Learning model can improve student learning activities, teacher teaching activities and student learning outcomes.